A nanoscale design approach for enhancing the Li-ion conductivity of the Li10GeP2S12 solid electrolyte - Dawson, JA; Islam, MS (American Chemical Society, 2022)
The discovery of the lithium superionic conductor Li10GeP2S12 (LGPS) has led to significant research activity on solid electrolytes for high-performance solid-state batteries. Despite LGPS exhibiting a remarkably high room-temperature Li-ion conductivity, comparable to that of the liquid electrolytes used in current Li-ion batteries, nanoscale effects in this material have not been fully explored. Here, we predict that nanosizing of LGPS can be used to further enhance its Li-ion conductivity. By utilizing state-of-the-art nanoscale modeling techniques, our results reveal significant nanosizing effects with the Li-ion conductivity of LGPS increasing with decreasing particle volume. These features are due to a fundamental change from a primarily one-dimensional Li-ion conduction mechanism to a three-dimensional mechanism and major changes in the local structure. For the smallest nanometric particle size, the Li-ion conductivity at room temperature is three times higher than that of the bulk system. These findings reveal that nanosizing LGPS and related solid electrolytes could be an effective design approach to enhance their Li-ion conductivity.